(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2023)
Some plants of the genus Pulicaria have been used in traditional medicines for treating back pain and inflammation. They possess various bioactivities such as antipyretic, analgesic, and hepatoprotective. This study aimed to investigate the potential analgesic, antipyretic, anti- inflammatory, and hepatoprotective activities of Pulicaria crispa (P. crispa) extract (PCE). Analgesic activity was evaluated using the hot plate and acetic acid-induced writhing tests. Antipyretic and anti-inflammatory activities were evaluated using rectal temperature and carrageenan-induced hind paw edema methods, respectively. CCl4-intoxication was used for hepatoprotective activity. Also, liver histopathology was assessed. PCE, at 500 mg/kg, exhibited significant analgesic, antipyretic, and anti-inflammatory effects. The increased serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT), and bilirubin of CCl4-exposed rats reflects their liver injury. PCE significantly decreased the elevated liver markers. The hepatoprotective effect of PCE was confirmed, as it successfully reversed the altered levels of total protein, malondialdehyde (MDA), and non-protein sulfhydryls (NP-SH) in the liver tissues of CCl4-exposed rats. Histopathological studies confirmed the hepatoprotective nature of PCE. Pretreatment of rats with PCE reduced the severity of CCl4-induced liver damage. These findings concluded that PCE possesses analgesic, antipyretic, anti-inflammatory, and hepatoprotective activities.